(3GOGQI GdJMOjGJ GdGSJQGJjLjI aj GdHfhcs - (3YdGA aQMGf(B, (3WGdHs ((3YeGf(B:s (3OGQ UaGA(B,s, 2009)
(3GdGWGQ GdfXQj hGdeaGgjej ddOQGSI, GdLGfH GdYdej ddOQGSI, GdGSJfJGLGJ hGdJhUjGJs
(3HHdjhZQGajG(B: (3U(B.279-312 (3edGMb U(B.218s
Keywords: (3GOGQI GdGYeGds; (3GdHfhcs; (3GdJNWjW GdESJQGJjLjs